Enhancing knowledge of authorization requests through registry development. Issue 2 (5th December 2017) - Kuntz‐Melcavage, Kara L.; Gahagan, Kyle DeCarlo; Fracasso, Mark R.; Marsteller, Jill A.
Abstract: Understanding the member population to which medical coverage policies apply is important for ensuring the relevance of a health insurer's policies. The medical policy unit of our company developed a registry and workflow to enhance our knowledge about the members who seek authorization for bariatric surgery. Data captured in the registry have allowed us to construct a descriptive profile of the entire population that seeks bariatric surgery (both members who are approved and members who are denied). In addition, we have examined characteristics associated with denied authorization requests, determined the proportion of requests originating from specific insurance products, and studied the relationship between results on a specific laboratory test and authorization decisions. Given the growing importance of data in the realm of health care management, this article is an important demonstration of how data can be used to understand populations of members who are affected by medical policies.